Ammonia stress decreased biomarker genes of acetoclastic methanogenesis and second peak of production rates during anaerobic digestion of swine manure. (December 2020) - Yu, Dawei; Zhang, Junya; Chulu, Buhe; Yang, Min; Nopens, Ingmar; Wei, Yuansong
Graphical abstract: Highlights: Potential biomarker genes for early warning of ammonia inhibition were identified. Ammonia stress significantly impacted the second peak of methane production. Recovery over resistance is the key of acclimation to ammonia in acetate uptake. Ammonia competed CH3 -CO-Pi with CoA, inhibited pta in acetoclastic methanogens. Similar initial inhibition but different recovery observed in methanogenic pathways. Abstract: Research shows that anaerobic digestion could acclimate to ammonia stress; however, the acclimation remained unaddressed. In this study, evolution of microbial community, functional gene, and pathway was linked with apparent kinetic and performance in unacclimated inoculum under ammonia stress, to deepen understanding of the acclimation. The second peak in production rate demonstrated crucial kinetic changes under ammonia stress. The methane loss was mainly protein in residual COD. Metagenomic showed initial inhibition in all methane metabolism pathways under ammonia stress, and recovery in acetate uptake was the key to ammonia acclimation. The acclimation was found in alternative pathway of Acetyl-CoA (CH3 CO-S-CoA) synthesis from acetate, accompanying by syntrophic methanogenesis. Ammonia inhibited acetoclastic methanogenesis by competing CH3 -CO-Pi with pta and formed speculative sediment CH3 -CO-PO4 [NH4 ]2 . Biomarker of methanogenesis kinetic was suggested as mcr, hdr, and mch . The biomarker could indicate acclimation stages to ammonia, empowering anaerobic digestion by early warning of methane loss.